Annual variation of litterfall yield in the channel Furo Grande mangrove stands in Bragança, Pará - Gonçalves, Adriana do Socorro da Costa; Fernandes, Marcus Emanuel Barroncas; Carvalho, Muzenilha Lira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
This study was carried out at the Furo Grande, Bragança-Pará, which is characterized by three types of mangrove stands: one dominated by Rhizophora mangle, another by Avicennia germinans, and a third one being a mixed of both species. The study site presented a litter production of 7.47 t.ha-1.year-1 (year 1) and 7.11 t.ha-1.year-1 (year 2). Although the monthly variation was not statistically significant, this variation indicated a high litter production during the dry season (August to November/2000) and the end of wet season (May to July/2001). Leaves presented an average of 74% of the total production for both years, and it was the component which presented the highest contribution to the total production in all sites during the two years of study, with values that ranged from 65.5% (Site nº3 – year 1) to 78.4% (Site nº1 – year 2). There was a negative correlation between the litterfall production and the precipitation, indicating a strategy of energetic economy by leaf abscission in the dry season. The litterfall production presented a regular seasonal pattern, which tendency is expected to be repeated in the subsequent years.